The Use of Picture Storybooks in Blended-based Learning Method to Teach Literacy to Young Learners - Putu Ega Yudia Mastika; Ni Nyoman Padmadewi; Putu Adi Krisna Juniarta (Acitya: Journal of Teaching and Education, 2023)
This study aims to investigate the implementation of picture storybooks integrated with the blended learning method through LMS for young learners in fourth-grade students in English literacy learning. In this study, the researchers used an experimental design. The research chosen by the researchers is a post-test-only control group design. Document analysis and statistical analysis of students’ score was used to compare their literacy skills. The research sample was 70 fourth-grade students at SDN 3 Banjar Jawa Singaraja. The results showed that there were significant differences in students’ score while they learned English literacy using picture storybooks integrated with the blended-based learning method. The data obtained then tested using the independent sample t-test, the result showed sig. (2-tailed) is 0.011, which the observed significant level (sig. 2-tailed) is smaller than the standard alpha level (α=0.05). From the result obtained also showed that the use of picture storybooks integrated with the blended learning methods can help students learn in English literacy teaching. Therefore, the use of picture storybooks integrated with the blended-based learning methods is highly recommended because it has a significant influence on English literacy learning for young learners, besides it can also create fun and effective learning.